Comparison of physiological state and conditions imitating the comorbidity of type 2 diabetes with Alzheimer's disease. The impact on: proliferation, H2O2, Aβ42, S100A8, S100B levels, neuronal protrusion and neurogenesis - Adriana Kubis-Kubiak; Benita Wiatrak; Agnieszka Piwowar (Polskie Towarzystwo Farmaceutyczne, 2023)
Abstract Aim: Recent studies demonstrate that individuals with T2DM more likely to develop AD. While, disturbed glucose or insulin homeostasis, are at the forefront of AD research, not much is known about extra- and intracellular interplay between different forms of Aβ and microenviromental fluctuations of glucose or insulin concentrations in neuronal cells. Methods: We create conditions imitating the coexistence of T2DM with AD and compare the results with state where the neuropathological changes are yet not developed. We have investigated the effect of the physiological (Aβ40) and toxic amyloid form (Aβ25-35) and its co-incubation with glucose or insulin on neuronal proliferation, H2O2, Aβ42, S100B, S100A8 protein concentrations, mature neuronal protrusions and neurogenesis. Results: Aβ40 and Aβ25-35 with hyperglycaemia provoked stronger cytotoxic effect comparing to Aβ alone, while hyperinsulinemia dampen this effect. Opposite results were obtained in H2O2 measurement. Insulin stimulated Aβ42 generation when co-incubated with both Aβ forms. Aβ40 and Aβ25-35 caused similar pattern of extracellular S100B protein influx an concomitant cytosolic efflux. Neuronal protrusions and neurogenesis were initiated by co-incubation of Aβ40 with hyperglycaemia while reduced in Aβ25-35 and hyperglycemia or insulinemia. Significance: Our finding suggest that for understanding the biochemical origins of neuropathological amyloid β progression and potential involvement of metabolic disturbances in this process, it's crucial to gasp preliminary interactions on cellular level. Our data can lead to hypothesis that S100B protein could be a potential modulator as well as indicator of prodromal neuropathological alterations.